1978
DOI: 10.1577/1548-8659(1978)107<484:pemdoc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Morning Dissolved Oxygen Concentrations in Channel Catfish Ponds

Abstract: Consumption of O2by planktonic communities of pond waters may be predicted from chemical oxygen demand (COD) and temperature (r 2 -0.85). In ponds where planktonic organisms are the major source of turbidity, Secchi disk visibility may also be used to estimate COD (r 2 -0.81) or consumption of O2 by planktonic communities (r 2 = 0.82). A computer simulation model for nighttime decline in dissolved oxygen (DO) concentrations was developed for channel catfish ponds. This model incorporated data on plankton respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 1 publication
(1 reference statement)
1
25
1
2
Order By: Relevance
“…Further study is needed to make precise understanding about antibiotics effects on water quality parameters. Results was reported for temperature 22-37°C (Del Nery et al, 2013) and 25.8±1.0°C and pH 7.6±0.2 (Castine et al, 2012) and 6.2-9.2 (Losordo and Piedrahita, 1991), DO = 7±2 mg LG 1 (Boyd et al, 1978) and 3-5 mg LG 1 (Diana et al, 1991). Total hardness ranges from 822.33±1.52-769.66±2.08 mg LG 1 (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Further study is needed to make precise understanding about antibiotics effects on water quality parameters. Results was reported for temperature 22-37°C (Del Nery et al, 2013) and 25.8±1.0°C and pH 7.6±0.2 (Castine et al, 2012) and 6.2-9.2 (Losordo and Piedrahita, 1991), DO = 7±2 mg LG 1 (Boyd et al, 1978) and 3-5 mg LG 1 (Diana et al, 1991). Total hardness ranges from 822.33±1.52-769.66±2.08 mg LG 1 (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The DO values recorded by the data loggers would not have fallen below the threshold in that short amount of time. This is supported by the Boyd et al (1978) model in which their predicted and measured DO (mg/L) did not begin to approach critical levels until into the early morning hours because the decline was linear over time. The OZ volume began to decline over the night and reached the lowest levels in the early morning.…”
Section: Discussionmentioning
confidence: 83%
“…As only one depth was sampled in this study, the results presented here represent an approximation of NPP and WPR. The general approach was similar to that described by Boyd et al (1978), who demonstrated the accuracy of a projection technique based on an assumed linear nocturnal decline in DO concentration.…”
Section: Methodsmentioning
confidence: 97%